Pengaruh Halal Atribut dan Citra Destinasi Wisata terhadap Niat Berkunjung Kembali di Kota Padang Panjang - Sari, Nia Mutiara; Wulandari, Dwi Pratiwi (JES (Jurnal Ekonomi Syariah), 2024)
This research was motivated by the researcher's observations regarding intention to return to the Padang Panjang City tourist destination. Where there is a lack of tourist interest in visiting the Padang Panjang City tourist destination again. This research aims to analyze the impact of halal attributes and image of tourist destinations on intention to return to Padang Panjang City. This study has a quantitative descriptive design, with a sample size of 399 respondents determined by applying the Slovin formula and a purposive sampling strategy. A Likert scale questionnaire that has undergone validity and reliability testing is the method used in this study to collect data. Using the SPSS version 26 computation tool, the obtained data was subjected to multiple linear regression analysis. Based on the analysis's findings, inferences may be made about the halal attribute variable (X1) using the t test results, which show a significant influence of halal attributes on intention to return at a significant level of 0.000<0.05. Concurrently, halal attributes (X1) and tourist destination image (X2) have a substantial impact on intention to visit again, according to the findings of the t test for the variable tourist destination image (X2), which has a significant level of 0.007<0.05. The intention to return (Y) variable is influenced by the halal attribute (X1) and tourist destination image (X2) variables by 17.3% and other variables by 82.7%, respectively.